The Responsibility of the Indonesian State Toward Indonesian Citizens Involved in Acts of Terrorism Abroad - Muradi, Muradi; Januarsyah, Mas Putra Zenno (Universitas Sultan Ageng Tirtayasa, 2025)
The phenomenon of Indonesian citizens (WNI) becoming involved in acts of terrorism abroad necessitates a legal assessment of the state’s responsibility under international law. This study employs a qualitative method with a normative juridical approach to analyze the obligations of the state in addressing its nationals who are part of global terrorist networks. Key principles of international law—such as due diligence, non-refoulement, and the duty to prevent and suppress transnational terrorism—form the core focus of this analysis. The study also evaluates Indonesia’s policy towards former ISIS-affiliated citizens, highlighting dilemmas surrounding citizenship revocation and the repatriation of returnees. Furthermore, multilateral cooperation mechanisms, including the ASEAN Convention on Counter-Terrorism (ACCT) and United Nations Security Council resolutions, are examined as part of Indonesia’s counter-terrorism strategy. The findings emphasize the importance of balancing national security interests with the protection of human rights and strengthening international legal diplomacy to ensure effective and globally aligned counter-terrorism efforts.